2016
DOI: 10.1007/s12541-016-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultra-thin SnO2 coating on Pt catalyst for energy applications

Abstract: In this paper, we present a simple and novel approach for stabilizing a porous metal-based nanostructure through atomic layer deposition in which ultra-thin tin oxide (SnO 2 ) coats platinum (Pt) film. After heating the ultra-thin tin oxide-coated Pt samples at 300 o C and 500 o C and observing the in situ sheet resistance variations of Pt for 20 hours, we found that the ultra-thin tin oxide coating suppresses metal agglomeration. The thermal stability of ultra-thin tin oxide-coated Pt was greater than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Another type of ALD oxide, SnO 2 , was demonstrated as an overlayer for the Pt cathode; Chang et al investigated ALD SnO 2 coating on Pt for stabilizing a porous metal-based nanostructure. They observed the improvement in thermal stability, but not in cathodic activity, at 300-500°C [29].…”
Section: Cathodementioning
confidence: 96%
See 2 more Smart Citations
“…Another type of ALD oxide, SnO 2 , was demonstrated as an overlayer for the Pt cathode; Chang et al investigated ALD SnO 2 coating on Pt for stabilizing a porous metal-based nanostructure. They observed the improvement in thermal stability, but not in cathodic activity, at 300-500°C [29].…”
Section: Cathodementioning
confidence: 96%
“…Nanoporous structures of metals and ceramic, in combination with nanoparticles, are employed. However, the mechanical and chemical stability of electrode structures with high surface-to-volume ratio, especially nanostructures, may become a serious issue at elevated temperatures [27][28][29][30][31][32][33].…”
Section: Losses In Sofc With Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…One interesting way to enhance the thermal stability of noble metal electrodes for low‐temperature SOFCs is by the oxide overcoating method. Previous studies observed that a zirconia (ZrO 2 ), ceria (CeO 2 ), or tin oxide (SnO 2 ) capping layer formed using thin film deposition techniques, for example, sputtering, atomic layer deposition (ALD), on nano‐porous metal electrodes can protect the nano‐porous Pt cathode morphology from thermal agglomeration . Su et al showed that an ALD ZrO 2 over‐layer (1 nm) on a Pt electrode improved the lifetime of the electrode by nearly 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Reported methods to maintain the high density of nanoporous features of pure Pt electrode include electrode surface-capping by a thin layer of oxide, 44,46,57 employing the core-shell structure of the nanoparticles, 80 or alloying with another catalytically active element such as nickel 49 or ruthenium. 48 Pt.…”
Section: Chapter 4 4 Thermal Stability Enhancement Of Nanoporous Catmentioning
confidence: 99%